Friction Characterization of Al-Si Coated Ultra-High Strength Steel under Hot Stamping Conditions. Issue 1 (June 2021) - He, R; DiCecco, S; George, R; Worswick, M; Chiriac, C; Luckey, G; Tjong, J; Shi, C; Boettger, J
Abstract: Friction characterization of a hot stamped 1, 800 MPa Al-Si coated ultra-high-strength steel (UHSS) is considered. Quantification of the coefficient of friction during a hot stamping process is essential for an accurate constitutive finite element model. The current work considers the twist compression test (TCT), in which an annular cup rotates against the surface of a fixed specimen using heated tooling. The measured sliding force and normal force determine the coefficient of friction. The test conditions used in this research simulate thermo-mechanical histories operative during hot stamping. Specimens are austenitized in a chamber furnace at a nominal temperature of 930 °C and a hold time of 5 minutes. They are then transferred to the TCT apparatus in which frictional sliding and die quenching occur simultaneously. The tooling components are uncoated and heated to 80 °C. Contact pressure of up to 30 MPa was considered between the tooling and specimen and a sliding speed of up to 38 mm/s. An increase in contact pressure caused the coefficient of friction to increase during dynamic friction. On the other hand, changes in sliding speed did not have a significant impact on the coefficient of friction. Likewise, repeated tests on the same tooling surface show that the coefficient of friction remains consistent during tool wear. Surface roughness of the tooling only increased after the first test and then remains stable during subsequent tests.